Biology of Danaus chrysippus L. (Lepidoptera: Danaidae): feeding potentials in the larval host plants and adult nectar plants (Journal of Biodiversity Conservation and Bioresource Management, 2019)
The biology and feeding potential of plain tiger butterfly, Danaus chrysippus L. (Lepidoptera: Danaidae) were examined in both field and laboratory conditions from July 2011 to June 2012. Field collected singly laid eggs on host plant (Asclepias curassavica) were reared in the laboratory at room temperature (25 ± 3 °C) and 70 ± 5% RH. Various life stages of the butterfly, viz. egg, larvae, pre-pupa, pupa and adult have been described. The egg incubation period was 4.6 ± 0.8 days; the duration of larval stages from 1st to 5th instars were 1.7 ± 0.2, 2.2 ± 0.2, 2.5 ± 0.3, 2.7 ± 0.2 and 3.1 ± 0.4 days, respectively; pre-pupal period was 1.4 ± 0.4 days; pupal period was 8.6 ± 1.1 days; the longevity of the adult females was 7.8 ± 0.3 days and of the males was 10.4 ± 0.7 days. The larval lengths of each of the five instars were 3.7 ± 0.84, 8.7 ± 1.09, 14.3 ± 1.20, 23.2 ± 2.36 and 38.5 ± 2.54 mm, respectively. The feeding potential rates of the five instar larvae were 5.5 ± 1.11%, 22.8 ± 2.96%, 67.7 ± 2.99%, 96.8 ± 4.09% and 293.6 ± 15.9%, respectively. The weights (in gram) of the excreta of five larval instars were 0.06 ± 0.02, 0.13 ± 0.03, 0.54 ± 0.06, 0.81 ± 0.06 and 1.96 ± 0.09, respectively. A total of 187 individuals was observed on 16 potential nectar plants in the Butterfly Research Park (BRP), Gazipur. These were Lantana camara, Asclepias curassavica, Duranta plumeri, Hibicus rosa sinensis, Duranta repens, Tagetes patula, Ixora chinensis, Heliotropium indicum, Cosmos bipinnatus, Wedelia calendulaca, Punica hybrida, Spilanthes calva, Leucas linifolia, Helianthus annus, Euphorbia pulcherrima and Gomphera globosa. Among these, L. camara was visited most frequently (16.58%) and L. linifolia was least frequently (1.60%) by this butterfly. No Danaus chrysippus was observed visiting H. annus and E. pulcherrima plants.J. Biodivers. Conserv. Bioresour. Manag. 2019, 5(1): 121-132